Case report: A case of immune thrombocytopenia combined with Hashimoto's thyroiditis and Helicobacter pylori infection in a child - Yang, Lihong; Xiao, Dongqiong; Li, Xihong; Lai, Chunqi; Chen, Yuhao; Pan, Lingli (Frontiers in Pediatrics, 2023)
Immune thrombocytopenia (ITP) is one of the most prevalent acquired bleeding disorders in children, which is primarily characterized by a decrease in platelet count. It can be classified into two subtypes: primary ITP and secondary ITP. The underlying mechanisms causing ITP are complex and not fully comprehended. Helicobacter pylori (H. pylori) infections can lead to ITP and potentially trigger various autoimmune diseases. Furthermore, there is evidence of a correlation between thyroid disease and ITP. In this case report, we describe the case of an 11-year-old patient who presented with ITP, Hashimoto's thyroiditis (HT), and H. pylori infection. Following anti-H. pylori treatment and thyroxine supplementation, the child's platelet count increased compared to the previous count. The limitation of this report is that the platelet count of this child returned to normal after anti-H. pylori and thyroxine supplementation, so we cannot distinguish the effect of anti-H. pylori and thyroxine supplementation on the platelet count in this child. Despite this limitation, we still believe that early screening for thyroid function and H. pylori, as well as prompt eradication of H. pylori, along with thyroxine supplementation, may be beneficial in treating and improving the prognosis of children diagnosed with ITP.